Measuring competence, self-reported competence and self-efficacy in pre-registration students - William Lauder; Karen Holland; Michelle Roxburgh; Keith J. Topping; Roger Watson; Martin Johnson; Mary Porter; Agnieszka Behr (2008)
Aim To measure competence, self-reported competence and self-efficacy; explore any differences between cohorts and student entry criteria; and explore the relationship between competence, self-reported competence, support and self-efficacy. Method All students undertook a three-station objective structured clinical examination (OSCE) and had previously completed a questionnaire, which included measures of self-reported competence, support and self-efficacy. The performance of two single year cohorts enabled measurement of competence development and progression. Results Students were competent in the core generalist skills of communication and hand decontamination but demonstrated low levels of numeracy. Conclusion Doubts are raised about the explanatory value or practical use of social cognitive theory in pre-registration curricula and questions are raised about the value of self-reported competence. This has implications for nursing and midwifery curricula, which emphasise the importance of self-assessment.